2019
DOI: 10.48550/arxiv.1910.14646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational pseudorandomness, the wormhole growth paradox, and constraints on the AdS/CFT duality

Abstract: A fundamental issue in the AdS/CFT correspondence is the wormhole growth paradox. Susskind's conjectured resolution of the paradox was to equate the volume of the wormhole with the circuit complexity of its dual quantum state in the CFT. We study the ramifications of this conjecture from a complexity-theoretic perspective. Specifically we give evidence for the existence of computationally pseudorandom states in the CFT, and argue that wormhole volume is measureable in a non-physical but computational sense, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 23 publications
(47 reference statements)
6
43
0
Order By: Relevance
“…Since entropy is an important quantity of interest in AdS/CFT, we discuss potential implications of our result for this duality 21 In particular we propose a gedankenexperiment based on our results that gives evidence for certain instances of AdS/CFT having the AdS dictionary be computationally intractable to compute, unless LWE is tractable. A similar result was obtained by Bouland et al [BFV19], in the context of the wormhole growth paradox. Their result also uses cryptographic techniques in the form of pseudorandom quantum states.…”
Section: Applications To Holographysupporting
confidence: 88%
See 1 more Smart Citation
“…Since entropy is an important quantity of interest in AdS/CFT, we discuss potential implications of our result for this duality 21 In particular we propose a gedankenexperiment based on our results that gives evidence for certain instances of AdS/CFT having the AdS dictionary be computationally intractable to compute, unless LWE is tractable. A similar result was obtained by Bouland et al [BFV19], in the context of the wormhole growth paradox. Their result also uses cryptographic techniques in the form of pseudorandom quantum states.…”
Section: Applications To Holographysupporting
confidence: 88%
“…That is, in some sense, quantum gravitational systems cannot be simulated efficiently by a quantum computer. Bouland, Fefferman and Vazirani have also explored this challenge to the thesis from the perspective of the wormhole growth paradox using the tools of computational complexity [BFV19]. In particular, they showed that one can prepare computationally pseudorandom states on the boundary CFT.…”
Section: Discussion and Open Questionsmentioning
confidence: 99%
“…Finally we would like to discuss observational difficulties in detecting the Python's lunch degrees of freedom (see [50] for some related discussions). In our setup, a computationally bounded observer performs relatively simple operations that are limited to the Hilbert space H i introduced above.…”
Section: Complexity Reconstruction and Ghostly Interactionsmentioning
confidence: 99%
“…This is of theoretical interest as it shows an alternative way for achieving quantum pseudorandomness which is different from current approaches based on post-quantum and computational assumptions. Apart from the cryptography perspective, having a different set of assumptions for PRS and PRU can find potential applications in physics [44]. Another interesting future direction would be to further explore the relationship between unclonability and quantum pseudorandomness that has been initially proposed in [9], relying upon our new results.…”
Section: Conclusion and Discussionmentioning
confidence: 93%